Properties of the nucleotide binding sites of the Ca²⁺-ATPase of sarcoplasmic reticulum - Jeans, David Richard (Division of Chemical Pathology, 2017)
Properties of the nucleotide binding site of the Ca²⁺-ATPase of skeletal muscle sarcoplasmic reticulum have been investigated. The study centred around interaction of the high affinity ATP analog, 2'-3'-0-(2,4,6-trinitrophenyl)adenosine 5'-triphosphate, (TNP-ATP), with the Ca²⁺-ATPase. Defined fractions of the sarcoplasmic reticulum (SR), corresponding to the terminal cisternae (TC) and light SR (LSR), were isolated. The TC were shown to have distinctive morphological characteristics that differ from the LSR. The TC vesicles contained electron dense intravesicular material representative of Ca²⁺ binding proteins, and visible membranous "feet" structures, which are reported to interconnect with the transverse tubule. Functional characterisation of the isolated fractions provided evidence for the predominant localisation of Ca²⁺ release channels in TC, and concentration of Ca²⁺-ATPase molecules in LSR. These conclusions were based on the following observations: (a) decreased Ca²⁺ transport of TC versus LSR; ruthenium red, a Ca²⁺ channel blocker, enhanced Ca²⁺ transport and pumping efficiency in TC, (b) higher Ca²⁺-ATPase activity for LSR in the presence and absence of ionophore, (c) rapid Ca²⁺ efflux from TC which is inhibited by ruthenium red. Of special interest was the characterisation of the TC and LSR with respect to turnover-dependent TNP-ATP fluorescence. Fluorescence observed for TC was approximately 65% of that for LSR. This phenomenon may be attributable to either the decreased Ca²⁺ ATPase content of the TC vesicles or open Ca²⁺ release channels. Hence the TNP-ATP fluorescence characteristics appear to reflect the morphological and functional subspecialisation of the defined SR fractions.